Brazilian test approach to minimise conditioning period and maximise ingress of harmful materials for durability of fibre-reinforced concrete. (March 2014) - Kim, B; Roque, R; Kim, N-H; Lee, J-Y
This article compares the test results of the conventional beam approach to those of the Brazilian test related to the durability of fibre-reinforced concrete. The flexural test was found to have some limitations for durability evaluation. On the other hand, the Brazilian test was found to have unique advantages for ingress of saltwater solutions in a short period of time and obtained relatively uniform stress distributions at the failure surface. The evaluation of the rate of stiffness reduction showed that polyvinyl alcohol fibres in saltwater solutions have the weakest resistance to crack propagation and polypropylene fibres have the greatest. The observed fracture surfaces after testing were found to have a uniformly damaged surface and first cracks were exactly initiated at the centre of the crack tip.